Nutrition for European elite fencers: A practical tool for coaches and athletes - Lomazzi, M. (Nutrients, 2024)
The aim of this narrative review is to create a comprehensive, innovative, and pragmatic resource to guide elite fencers and coaches in making strategic nutritional choices to enhance performance and facilitate recovery. The literature review identified only 12 articles specifically addressing the topic of nutrition for fencers. Thus, the recommendations provided in this review derive also from articles dealing with similar sports, such as martial arts, and from investigations with European elite fencers and their coaches. For elite fencers, it is suggested to consume daily 7-11 g/kg of body weight (BW) of carbohydrates and 1.5-2 g/kg of BW of proteins and allocate 25% to 30% of the total energy intake to essential fats, with a specific focus on omega-3 fatty acids. The timing of meals, ideally within one hour after exertion, plays a pivotal role in restoring glycogen reserves and preventing injuries. The intake of leucine, creatine, omega-3, collagen, and vitamins C and D is proposed as a strategy for injury recovery. It is worth acknowledging that even when personalized plans are provided, implementation can be challenging, especially during competitions and training camps.